Keanekaragaman Jenis Gulma Invasif di Vak Gymnospermae Kebun Raya Bogor - Rizki Wulan Anjani; Eko Purnomo; Muhammad Rifqi Hariri (Yayasan Literasi Sains Indonesia, 2023)
Weeds are botanical organisms deemed undesirable within a designated planting area due to their potential to diminish the value of cultivated plants and engender competition with the primary crop. The coexistence of weeds with primary crops can exert a significant influence. The present study used an exploration method was conducted inside the Gymnosperms collection at the Bogor Botanic Gardens, specifically focusing on sections II.E, V.F, and XV.A. A total of 38 distinct weed species exist, belonging to 25 different plant families. Among these groups, the two most prominent ones are Asteraceae and Commelinaceae. One of the numerous contemporary approaches to weed management involves the utilization of herbicides, as this strategy is widely seen as more effective in terms of cost, time, and labor efficiency.